THE ROLE OF THE ARCTIC RESOURCE CORPORATIONS IN INNOVATION PROCESSES AND SUBSTITUTION - V. Selin; V. Tsukerman (Модернизация, инновация, развитие, 2016)
The study is particularly mining companies located in the Russian Arctic. The main results of the study include the rationale for the demand for products Arctic mineral corporations and retain their capitalization, even in conditions of «sanctions» policy of the West. The main fi eld of application of the obtained results is the formation of industrial policy resource corporations, including at the regional level. At the heart of the industrial policy of the Russian Arctic are the principles of strategic import substitution. While Arctic mineral corporations may be, including in the implementation of the Arctic mega-projects on the principles of state-private partnership, «the locomotive» the dynamics of innovation in the economy.